A Convergent Synthesis of the Triterpene Saponin Asiaticoside. Issue 9 (10th May 2017) - Shao, Wenbo; Cao, Xin; Shen, Lei; Zhang, Fuyi; Yu, Biao
Abstract: Asiaticoside (1 ), namely, 2α, 3β, 23‐trihydroxy‐urs‐12‐en‐28‐oic‐ O ‐α‐l ‐rhamnopyranosyl‐(1→4)‐β‐d ‐glucopyranosyl‐(1→6)‐β‐d ‐glucopyranoside, the major active biomarker of the traditional medicinal plant Centella asiatica, has been synthesized for the first time. The strategy features a late‐stage gold(I)‐catalyzed glycosidic condensation of a triterpenoid acid and a trisaccharide ortho ‐hexynylbenzoate. The overall preparation required a total 31 steps with the longest linear sequence occurring over 14 steps in a 6 % overall yield and starting from ursolic acid (3β‐hydroxy‐urs‐12‐en‐28‐oic acid). Abstract : Ah, sugar sugar ! Asiaticoside, the major active biomarker of the traditional medicinal plant Centella asiatica, was synthesized in a convergent linear sequence over 14 steps in 6 % overall yield by starting from ursolic acid.